Engineering geology - Cox, Dave (New York, NY Magnum Publishing, 2016)
Engineering geology is the application of the geological sciences to engineering study for the purpose of assuring that the geological factors regarding the location, design, construction, operation and maintenance of engineering works are recognized and accounted for. Engineering geology studies may be performed during the planning, environmental impact analysis, civil or structural engineering design, value engineering and construction phases of public and private works projects, and during post-construction and forensic phases of projects. This book covers the fields of the earth sciences and engineering, particularly geological and geotechnical engineering. The focus of the book is on geological or engineering studies that are of interest to engineering geologists.
1. Geological and Geotourism Study of Iran Geology Natural Museum, Hormoz Island. -- 2. 3D Geology Modeling From 2D Prospecting Line Profile Map. -- 3. The Geological, Petrographical and Engineering Properties of Rhyolitic Tuffs (Çan Stone) in Çan-Etili Area (Çanakkale), Nw Turkey: Their Usage as Building and Covering Stones. -- 4. The Caucasian-Arabian Segment of the Airplane-Himalayan Collisional Belt: Geology, Volcanism and Neotectonics. -- 5. Application of Geomorphology, Tectonics, Geology and Geophysical Interpretation of, East Kom Ombo Depression, Egypt, Using Landsat Images. -- 6. The Age And Origin Of The Pacific Islands: A Geological Overview. -- 7. Seismic Microzonation of Breginjski Kot (Nw Slovenia) Based On Detailed Engineering Geological Mapping. -- 8. Geology and Geochemistry of Recent Sediments From the Mediterranean Sea: Sediment Texture of Northeastern Mediterranean Basin. -- 9. Reconstruction of the Lacustrine Delta and Lake Level Change Analyzing Subsurface Geology and Geomorphology: Changes That Occured During The Holocene In The Oguraike Reclaimed Land Area, Southern Kyoto, Japan. -- 10. Morphology, Geology and Water Quality Assessment of Former Tin Mining Catchment. -- 11. Geological and Tectonic Implications Obtained From First Seismic Activity Investigation Around Lembang Fault. -- 12. The Geotechnical Characteristics of Landslides on The Sedimentary and Metamorphic Terrains of South-East Nigeria, West Africa. -- 13. Geology, Geochemistry and Tectonic Setting of Pan-African Serpentinites of Um Salim -Um Salatit Area, Central Eastern Desert, Egypt. -- 14. Influence of Weathering on the Engineering Properties of Dacites in Northeastern Turkey. -- 15. Geology of London, UK. -- 16. Evaluation of The Influence Caused by Tunnel Construction on Groundwater Environment: A Case Study of Tongloushan Tunnel, China. -- 17. The Sun-Earth Connect 3: Lessons From The Periodicities of Deep Time Influencing Sea-Level Change and Marine Extinctions in the Geological Record.
Keywords: Engineering geology